Some Trace Elements and Oxidative Stress Status in Patients with Chronic Rheumatoid Arthritis - Abd Alameer, Noor; Alammar, Haider (Journal of Biomedicine and Biochemistry, 2023)
Background Rheumatoid arthritis (R.A.) is a complex polygenic, au- toimmune inflammatory disease. It was disturbing that almost 1-2% of people depended on that geographic spreading worldwide. R.A. can result from the interaction of genetic, environmental, and autoimmunity. It is characterized by non-organ-specific self-reactive antibody production and chronic synovitis leading to the damage of cartilage and bone. Objectives To evaluate the sera of trace elements and oxidative stress levels in patients detected with chronic rheumatoid arthritis. Determination of some trace elements such as copper, zinc, and iron in the sera of patients.Patients and Method A case-control study was done on the Iraqi population from Al-Najaf, an Iraqi city. Blood samples were collected from 135 volunteers from September 2021 to February 2022 from Al-Sadder Medical City (Al-Najaf). The 180 volunteers in our study were divided into two groups patient group consisting of 90 individuals ages range: (20–70 years), male and female, and a control group consisting of 45 individuals. Blood was drawn from the patients to measure the copper, zinc, and iron concentration level using the Colorimetric method technique.Results The average zinc concentration was lower in the patient’s group than in the reference category. The average copper concentration was more significant in the patient’s group than in the reference category. In addi- tion, the average Zn/Cu ratio was lower in the patient’s group compared to the reference category. There was no statistical variation in average serum iron between patients and the reference category. However, the average Zn/Fe ratio was lower in the patient’s group compared to the reference category control group.Conclusion Lower levels of zinc and a higher level of copper suggest a role for those trace elements on that pathogen of R.A.